Fenomena Pindah Agama Di Desa Ngadirejo Untuk Mendapatkan Legalitas Perkawinan Perspektif Maqāṣid al-sharī’ah - Abidah, Hany; Ulya, Zakiyatul (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2025)
This research is motivated by the phenomenon of religious conversion to obtain legal marriages that occurs in the Ngadirejo Village community. In response to the prohibition of interfaith marriages in positive law and Islamic law in Indonesia, couples of different religions choose to convert so that their marriages can be legally recognized temporarily. While Islamic jurisprudence (fiqh) has regulated invalid marriages, it has not explicitly explained the provisions for couples who convert to obtain legal marriages. The results of this study indicate that the phenomenon of religious conversion in Ngadirejo Village involves temporarily converting to obtain legal marriage, then returning to the original religion after the marriage is consummated. This decision is made due to religious differences between couples, local customs that require men to follow women, and the need for practical solutions to overcome administrative obstacles. And the phenomenon of changing religions to obtain legal marriage in Ngadirejo Village is contrary to the maqāṣid al-sharī’ah of Asy-Syathibi because it is not in accordance with the objectives of sharia, namely ḥifẓ al-dīn, ḥifẓ al-nafs, ḥifẓ al-'aql, ḥifẓ al-naṣl, and ḥifẓ al-māl.